TCAD optimization of LGAD sensors for extremely high fluence applications. (1st January 2023) - Croci, T.; Morozzi, A.; Sola, V.; Asenov, P.; Fondacci, A.; Giordanengo, S.; Borghi, G.; Vignali, M.C.; Paternoster, G.; Boscardin, M.; Menichelli, M.; Cartiglia, N.; et al.
Abstract: The next generation of high-energy physics experiments at future hadronic colliders will require tracking detectors able to efficiently operate in extreme radiation environments, where expected fluences will exceed 1 × 10 17  neq /cm 2 . This new operating scenario imposes many efforts on the design of effective and radiation-resistant particle detectors. Low-Gain Avalanche Diode (LGAD) represents a remarkable advance because the radiation damage effects can be mitigated by exploiting its charge multiplication mechanism after heavy irradiation. To obtain the desired gain (about 10–20) on the sensor output signal, a careful implementation of the "multiplication" region is needed (i.e.  the high-field junction implant). Moreover, a proper design of the peripheral region (namely, the guard-ring structure) is crucial to prevent premature breakdown and large leakage currents at very high fluences, when the bias voltage applied creates an electric field higher than 15 V/μm. In this contribution, the design of LGAD sensors for extreme fluence applications is discussed, addressing the critical technological aspects such as the choice of the active substrate thickness, the gain layer design and the optimization of the sensor periphery. The impact of several design strategies is evaluated with the aid of Technology-CAD (TCAD) simulations based on a recently proposed model for the numerical simulation of radiation damage effects on LGAD devices.